Journalism education curriculum in Malaysia: A preliminary study in a Malaysian public university - Aripin, Norizah; Ismail, Awan; Yusof, Norhafezah; Ismail, Rizalawati; Mohamad, Noraihan (Elsevier Ltd., 2014)
The research aims to develop an instrument on perception and expectation of journalism students in Malaysia.The pilot study employs survey research method.The questionnaires were distributed to 30 journalism students in Universiti Utara Malaysia. The data was analyzed based on reliability, validity and descriptive analysis.The findings indicated the instrument is valid and reliable.The majority of the respondents perceived that knowledge and expectations of journalism education are pertinent in developing knowledge and skills of journalism students. Nonetheless, facilities offered need to be enhanced to match the minimum requirement of journalism learning.